Design And Development Of New Clamping Method For Waterjet Machine (JetCLAMP) Based On Machining Performances - Ab Wahab, Norfariza; Mohd Shuhada, Muhammad Khusyairi; Nordin, Abd Khahar; Md Basar, Mohd Farriz; Boejang, Hambali; Mohd Najib, Suhaila; Mohd Nor, Rozilawati (IJENS Publisher, 2018)
Water-jet machine is commonly used in industry. This kind of machine can be operates in many types of design and material of product. Generally, there are two types of waterjet machining which is Water-jet Machining (WJM) and Abrasive Water-jet Machining (AWJM). The objective of this study is to develop a new method water-jet clamping for water jet machine. This work is focused on to produce and design a new clamping method for waterjet machine. Moreover, we proceed to choose suitable material can be uses to produce waterjet clamping. Furthermore, we have to analyze the efficiency of the clamp to hold the workpiece. Finally, to determine the capability of the clamp to hold various of thickness and the size of the workpiece. It is expected that the water-jet clamping can afford to clamp the workpiece in various of thickness and size of the workpiece. In conclusion, through this project we have to produce a new clamping method for water-jet which is to fulfill industry requirement.